From a bispecific monoclonal antibody to gene therapy: A new era in the treatment of hemophilia A - Mihaila, Romeo Gabriel (Biomedical papers, 2023)
The treatment of hemophilia A has progressed amazingly in recent years. Emicizumab, a bispecific-humanized monoclonal antibody, is able to improve coagulation by bridging activated factor IX and factor X. Emicizumab is administered subcutaneously and much less often compared to factor VIII products. It has low immunogenicity, does not require dose adjustment, and can be administered regardless of the presence of factor VIII inhibitors. Thrombin generation assays but not factor VIII activity are indicated to guide and monitor the treatment. Emicizumab has enabled the conversion of patients with severe forms into patients with milder forms of hemophilia A. It has reduced the number of bleeding episodes compared to both on-demand and prophylactic substitution therapy and has an excellent safety profile. Gene therapy can elevate factor VIII plasma levels for many years after a single treatment course, could offer long-term protection from bleeding episodes, and minimize or eliminate the need for substitutive treatment with factor VIII concentrates. Gene therapy can provoke an immune response, manifested by an increase in common liver enzymes, that require immunotherapy. Long term monitoring is necessary to identify possible adverse effects. Future objectives are: the development of an ideal viral vector, the possibility of its re-administration, the use of gene therapy in hemophiliac children, and determining whether it can be successfully used to induce immune tolerance to factor VIII ceteri paribus. The future will determine the place of each type of treatment and group of patients for which it is indicated.
Keywords: adeno-associated viral vector; emicizumab; hemophilia A; lentiviral vector; valoctocogene roxaparvovec